2022
DOI: 10.1155/2022/4575416
|View full text |Cite
|
Sign up to set email alerts
|

Electrogalvanism in Oral Implantology: A Systematic Review

Abstract: Purpose. The objective of this work is to study galvanic corrosion of different couples of prosthetic and implant alloys through the realization of a systematic review. Materials and Methods. An electronic search was performed on Pubmed, Google Scholar, Scopus, ScienceDirect, EbscoHost, and Web of Science for published studies related to electrogalvanism in oral implantology. The keywords used were “dental implants” and “galvanic corrosion.” Two independent readers read the scientific articles. Results. From 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Surface roughness is very important for osseointegration of the implant (Amine et al, 2022). To investigate the topography of specimen surfaces, AFM images were used.…”
Section: Resultsmentioning
confidence: 99%
“…Surface roughness is very important for osseointegration of the implant (Amine et al, 2022). To investigate the topography of specimen surfaces, AFM images were used.…”
Section: Resultsmentioning
confidence: 99%
“…The galvanic current depends on the potential differences between dental alloys. According to the multiple in vitro studies, significant galvanic current may occur in the following galvanic couples: dental amalgam and cobalt-chromium alloy [ 93 , 94 ]; titanium alloy and dental amalgam [ 95 ]; nitinol archwire and titanium brackets [ 96 ]; nitinol archwire and iron brackets [ 96 , 97 ]; titanium dental implant and cobalt-chromium or nickel-chromium alloys [ 98 , 99 , 100 , 101 ]. Moreover, the surface area of metallic appliances should be taken into account.…”
Section: Factors Affecting the Risk Of Dental Alloys Side Effectsmentioning
confidence: 99%
“…In addition, studies have shown that differences between metals (implant and abutment) can generate galvanic currents when in contact with saliva [ 34 , 35 ]. To avoid this phenomenon, it is prudent to follow the proposed recommendations, using different metals and always opting for the choice of the pairs titanium/titanium [ 36 ]. Another important point to be considered is the accuracy of adapting the abutments to the implant as a factor that can reduce mechanical and biological complications.…”
Section: Introductionmentioning
confidence: 99%